2014
DOI: 10.1007/s10488-013-0532-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perceptions of Using a Smartphone App with Prolonged Exposure Therapy

Abstract: Clinician perceptions of clinical innovations affect their adoption and spread. This study investigated mental health clinicians' (n = 163) perceptions of a patient-facing smartphone application (app) for prolonged exposure (PE) therapy for posttraumatic stress disorder, before its public release. After reading a description of the app, participants rated perceptions of it based on diffusion of innovations theory constructs. Perceptions were generally favorable regarding the app's relative advantage over exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…With regard to mobile apps “PFA Mobile” is a preventive mobile app developed for responders who provide Psychological First Aid (PFA), an evidence-informed approach for assisting individuals in the aftermath of disaster or emergencies (Kuhn, Eftekhari, et al, 2014 ). The app is not intended to replace PFA training and efficacy still needs to be shown.…”
Section: M-health Developments For Traumatic Stressmentioning
confidence: 99%
“…With regard to mobile apps “PFA Mobile” is a preventive mobile app developed for responders who provide Psychological First Aid (PFA), an evidence-informed approach for assisting individuals in the aftermath of disaster or emergencies (Kuhn, Eftekhari, et al, 2014 ). The app is not intended to replace PFA training and efficacy still needs to be shown.…”
Section: M-health Developments For Traumatic Stressmentioning
confidence: 99%
“…Rather, the focus of activity has been on development and dissemination of new mhealth applications (apps) designed to facilitate delivery of EBT's for PTSD and related disorders. These include two widely disseminated EBT's for PTSD, Prolonged Exposure (Kuhn et al, 2015;Kuhn et al, 2014;Reger et al, 2013) and Cognitive Processing Therapy (CPT Coach), in addition to EBP apps for common PTSD-related symptoms, such as insomnia (Koffel et al;Kuhn et al, 2016), depression (Acceptance and Commitment Therapy: ACT Coach and problemsolving: Moving Forward), and smoking cessation (Stay Quit Coach). Kuhn and colleagues (2015) evaluated adjunctive use of the PE Coach patient-facing smartphone app by 271 mental health clinicians trained in use of PE.…”
Section: The Role Of Mobile Technology In Clinician Training and Ebt mentioning
confidence: 99%
“…Prior work demonstrated that among patients, demographic characteristics and prior experience is largely unrelated to willingness to use technology for healthcare (Price et al., ). There is evidence, however, to suggest that prior use is relevant for clinicians (Kuhn et al., ). Clinicians with experience using mobile devices or who own a personal mobile device were more receptive to use such technologies in treatment.…”
Section: Discussionmentioning
confidence: 99%